Antioxidant Activity Of L - Theanine On Cadmium Induced Oxidative Stress Mediated Neurodegeneration - An In Vivo Analysis - Souparnika. V,; Karthik Ganesh Mohanraj,; Vidya. S, (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction: L-theanine, an amino acid found in green tea, has antioxidant, anti-inflammatory, and neuromodulatory properties. It improves dopamine, gamma-aminobutyric acid (GABA), and serotonin levels in the central nervous system and decreases neuronal death and mitochondrial failure (CNS). A complicated chain of circumstances, such as excitotoxicity, calcium excess, and mitochondrial malfunction contributes to oxidative stress-mediated neurodegeneration. By focusing on neurotrophins, polyphenols have neuroprotective effects and support neuronal survival.Materials and Methods: Three groups of Wistar rats were assigned at random. Control group, Cadmium induction group, and L-theanine therapy group. Group I: Rats were given a dosage of 150 mg/kg body weight to induce cadmium. L-theanine was administered orally for 30 days at a dose of 100 mg/kg body weight after 60 days of lead induction. Rats were euthanized at the conclusion of the experiment, and the brain tissues were removed, fixed in 4% paraformaldehyde, and processed for histological examination. Using SPSS software, bar graphs for SOD and LPO levels were plotted.Results: Group-II (Cadmium induced) rats showed neurodegeneration with severe neuronal damage, apoptotic and pyknotic neurons and gliosis. SOD levels were significantly decreased and MDA levels were significantly increased in this group. Group-III (L-theanine treated) rats showed relatively better improvement in neuronal recovery and significant increase in SOD level and a decrease in MDA level after treatment.Conclusion: L-theanine can provide marked protective effects against cadmium induced brain dysfunction in rats through its neuroprotective and antioxidant properties on cadmium toxicity.